Positive electrode active material, positive electrode plate, battery monomer, battery and electric device
By introducing a cladding of bismuth and titanium elements into the positive electrode active material of the battery cell, the perovskite structure is formed, which solves the problem of fast capacity decay of the positive electrode active material, significantly improves the cycle life and storage life, and improves the structure Stability and rate performance.
Patent Information
- Application Number
- CN202310868430.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-14
AI Technical Summary
The capacity of the positive electrode active material of existing battery cells is too fast attenuated, resulting in short cycle life and storage life, making it difficult to meet stringent performance requirements.
The positive electrode active material structure is adopted including a core part and a cladding layer. The core part is LiNiaCobM(1-a-b)O2 compound. The cladding layer contains bismuth elements and titanium elements. The molar ratio of bismuth elements to titanium elements is 0.1 to 2.0:1 , a perovskite structure is formed to improve structural stability and ion conductivity.
It effectively improves the cycle life and storage life of the positive electrode active material, improves the structural stability and rate performance of the material, and enhances capacity.
Smart Images

Figure CN119315001A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a positive electrode active material, a positive electrode plate, a battery cell, a battery and an electrical device. Background Art
[0002] Battery cells are widely used because of their reliable working performance, no pollution, and no memory effect. For example, as environmental protection issues are increasingly valued and new energy vehicles become more popular, the demand for power battery cells will show explosive growth.
[0003] As battery cells are increasingly used, the requirements for battery cell performance are becoming increasingly stringent. Positive electrode active materials are an important component of battery cells, but due to the rapid capacity decay of positive electrode active materials, the cycle life and storage life of battery cells are relatively short. Summary of the invention
[0004] The present application provides a positive electrode active material, a positive electrode plate, a battery cell, a battery and an electrical device. The cycle performance and storage performance of the battery cell described in the present application can be improved.
[0005] In a first aspect, the present application embodiment provides a positive electrode active material, wherein the positive electrode active material comprises a core portion and a coating layer, wherein the core portion comprises a LiNi a Co b A compound of M(1-ab)O2, 0.9≤a<1.0, 0<b<0.1, and a+b<1.0, M includes at least one of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, La and Nb; the coating layer is coated on at least a portion of the surface of the core portion, the coating layer includes bismuth and titanium, and the ratio of the molar percentage of the bismuth element to the molar percentage of the titanium element is (0.1 to 2.0):1.
[0006] Therefore, the embodiment of the present application uses the layered transition metal oxide as the core, and a coating layer is coated on at least part of the outer surface of the core to form a core-shell structure. The coating layer can protect the core, reduce the risk of side reactions caused by direct contact between the layered transition metal oxide and the electrolyte in the core, and is conducive to improving the cycle life and storage life; and the coating layer includes bismuth and titanium elements, and on the basis of adjusting the molar percentage of the bismuth element to the molar percentage of the titanium element to be (0.1 to 2.0): 1, the bismuth element and the titanium element are more likely to form a perovskite structure, which is conducive to the embedding or extraction of lithium ions from the perovskite structure, and in the process of embedding or extracting lithium ions, the structure of the coating layer is relatively stable, the amplitude of the volume change is small, and the structural change of the positive electrode active material is reduced, which can effectively improve the overall structural stability of the positive electrode active material and improve the cycle life and storage life of the positive electrode active material when applied to a battery cell. The perovskite structure formed by the above materials has a very high ionic conductivity, which is conducive to improving the rate performance of the positive electrode active material.
[0007] In some embodiments, the ratio of the molar percentage of the bismuth element to the molar percentage of the titanium element is (0.1 to 1.0): 1. The molar percentage of the titanium element is the same as or even relatively higher than the molar percentage of the bismuth element, which is more conducive to the formation of a perovskite structure such as bismuth titanate.
[0008] In some embodiments, the coating layer includes at least one of bismuth titanate, lithium titanate and lithium bismuthate; optionally, the coating layer includes bismuth titanate. The coating layer containing the above materials can provide capacity for the positive electrode active material on the basis of improving the cycle life and storage life, thereby improving the overall capacity of the positive electrode active material.
[0009] In some embodiments, 0.9<a<0.98; optionally, 0.92≤a<0.98. The relatively high molar amount of nickel can significantly increase the capacity of the layered transition metal oxide, and in combination with the coating layer, can improve the overall structural stability of the positive electrode active material.
[0010] In some embodiments, b≥1-ab. The molar amount of cobalt Co is greater than the molar amount of the M element, which is beneficial to further stabilize the structure of the layered transition metal oxide, reduce the risk of cation mixing, and improve the cycle performance of the material; and Co can participate in the charge and discharge reaction in the operating voltage range of 2.8V to 4.25V, which is beneficial to improve the capacity.
[0011] In some embodiments, the core portion includes a LiNi 0.91 Co 0.05 M 0.04 O2、LiNi 0.92 Co 0.04M 0.04 O2、LiNi 0.92 Co 0.05 M 0.03 O2、LiNi 0.92 Co 0.06 M 0.02 O2、LiNi 0.93 Co 0.03 M 0.02 O2 and LiNi 0.93 Co 0.025 M 0.025 At least one compound in O2.
[0012] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the core is A%, the mass percentage of the coating is B%, 99≤A / B<1000; optionally, 99≤A / B<300. When the embodiments of the present application meet the above range, the protective effect of the coating on the core can be improved, the risk of the core being corroded by the electrolyte can be reduced, and the energy density can be improved.
[0013] In some embodiments, 99≤A<100; and / or 0<B≤1. When the embodiments of the present application meet the above ranges, the protective effect of the coating layer on the core can be improved, the risk of the core being corroded by the electrolyte can be reduced, and the energy density can be increased.
[0014] In some embodiments, the coating layer has a thickness of 1 nm to 100 nm. When the coating layer has a thickness within the above range, it can provide good protection for the core, improve the overall structural stability of the positive electrode active material, and the coating layer will not occupy too much space, which is beneficial to improving the energy density.
[0015] In some embodiments, the positive electrode active material satisfies at least one of the following conditions:
[0016] (1) The volume distribution particle sizes Dv10, Dv50 and Dv90 of the positive electrode active material satisfy the following conditions: 0.5≤(Dv90-Dv10) / Dv50≤1.5; optionally, 0.8≤(Dv90-Dv10) / Dv50≤1.4;
[0017] (2) The volume distribution particle size Dv50 of the positive electrode active material satisfies: 2.0 μm ≤ Dv50 ≤ 15 μm; optionally, 3 μm ≤ Dv50 ≤ 12 μm;
[0018] (3) The specific surface area of the positive electrode active material satisfies BET of 0.34 m 2 / g≤BET≤1.2m 2 / g; optionally, 0.5m 2 / g≤BET≤1.0m2 / g.
[0019] When the embodiments of the present application meet the above range, the structure of the positive electrode active material can be further stabilized, and the overall structural stability of the positive electrode active material is higher during the cycle process.
[0020] In some embodiments, the positive electrode active material includes polycrystalline aggregate particles; optionally, the primary particle size D1 of the polycrystalline aggregate particles satisfies: 0.1 μm ≤ D1 ≤ 0.4 μm; and / or the volume distribution particle size Dv50 of the polycrystalline aggregate particles satisfies: 4.0 μm ≤ Dv50 ≤ 15.0 μm. When the volume distribution particle size Dv50 of the positive electrode active material is within the above range, its particle size is relatively large, but not too large, which is conducive to capacity development and can improve its structural stability.
[0021] In some embodiments, the positive electrode active material includes single crystal particles or single crystal-like particles, and optionally, the primary particle size D2 of the single crystal particles or single crystal-like particles satisfies: 0.7 μm ≤ D2 ≤ 2.0 μm; and / or the volume distribution particle size Dv50 of the single crystal particles or single crystal-like particles satisfies: 2.0 μm ≤ Dv50 ≤ 4.0 μm. When the volume distribution particle size Dv50 of the positive electrode active material is within the above range, its particle size is relatively large, but not too large, which is conducive to capacity development and can improve its structural stability.
[0022] In a second aspect, the present application further proposes a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, and the positive electrode film layer includes the positive electrode active material as described in any embodiment of the first aspect of the present application.
[0023] In a third aspect, the present application further proposes a battery cell, wherein the battery cell comprises a positive electrode plate as described in any embodiment of the second aspect of the present application.
[0024] In a fourth aspect, the present application further proposes a battery, comprising a battery cell as described in any embodiment of the third aspect of the present application.
[0025] In a fifth aspect, the present application further proposes an electrical device, comprising a battery as described in any embodiment of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0027] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.
[0028] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.
[0029] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.
[0030] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0031] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0032] Figure 6 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0033] Figure 7 This is one of the SEM schematic diagrams of the positive electrode active material in Example A.
[0034] Figure 8 This is the second SEM schematic diagram of the positive electrode active material in Example A.
[0035] Fig. 9 This is the X-ray diffraction (XRD) pattern of the positive electrode active material in Example A.
[0036] The drawings are not necessarily drawn to scale.
[0037] The following are the descriptions of the reference numerals:
[0038] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;
[0039] 5. Battery cell; 51. Housing; 52. Electrode assembly;
[0040] 53. Cover plate;
[0041] 6. Electrical equipment. DETAILED DESCRIPTION
[0042] Below, the embodiments of the positive electrode active material, positive electrode sheet, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0043] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0046] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0047] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0048] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0049] A battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The positive electrode sheet includes a positive electrode active material that can provide active ions, and the negative electrode sheet includes a negative electrode active material. The separator is located between the positive electrode sheet and the negative electrode sheet to isolate the positive electrode sheet from the negative electrode sheet. Active ions such as sodium ions and lithium ions migrate between the positive electrode sheet and the negative electrode sheet through the electrolyte, thereby realizing the charging and discharging of the battery cell.
[0050] The contact interface between the active material and the electrolyte is a solid-liquid contact interface, where side reactions are likely to occur, causing the active material to be consumed or even destroyed, which may shorten the cycle life of the battery cell. In order to improve the cycle life of the battery cell, in the related art, it is hoped that by adding a film-forming additive to the electrolyte, the film-forming additive participates in the film-forming reaction on the surface of the active material, thereby protecting the active material; however, some film-forming additives have low solubility in the electrolyte and are difficult to be used by adding them to the electrolyte, so the cycle life of the battery cell cannot be effectively improved.
[0051] In view of the above problems, a metal salt is added to the negative electrode active material layer of the negative electrode plate in the embodiment of the present application. During the cyclic charge and discharge process of the battery cell, the metal salt can be dissolved in the electrolyte to a certain extent, and can participate in the film-forming reaction on the surface of the active material to form an interface film on the surface of the active material, thereby playing a good protective role for the active material and improving the cycle life of the battery cell.
[0052] As an important component of battery cells, the performance of positive electrode active materials largely determines the quality of battery cell performance. During the cyclic charge and discharge process of battery cells, positive electrode active materials are mainly used to provide active ions (such as at least one of sodium ions and lithium ions) required for the reciprocating intercalation and deintercalation between positive and negative electrode lithium compounds. Layered transition metal oxide materials have the advantages of high energy density, high reversible capacity, and environmental friendliness, so they are widely used in the battery field. Layered transition metal oxides contain nickel elements. Since Ni 2+ / Ni 3+ 、Ni 3+ / Ni 4+ The redox couple has a lower potential and more Li at 4.2 V + Therefore, as the nickel content increases, the capacity of the material can be effectively increased; however, as the nickel content increases, the Li + There is a risk of mixing up and resulting in reduced cycle life and storage life.
[0053] In view of the above-mentioned technical problems, an embodiment of the present application proposes a positive electrode active material, which includes a core portion and a coating layer, wherein the core portion includes a layered transition metal oxide material, and the coating layer includes bismuth and titanium elements. The coating layer can provide good protection for the core portion, and the coating layer has good structural stability during the battery cell cycle process, thereby further improving the overall structural stability of the positive electrode active material and improving the cycle life and storage life.
[0054] Positive electrode active material
[0055] In a first aspect, the present application embodiment provides a positive electrode active material, wherein the positive electrode active material comprises a core portion and a coating layer, wherein the core portion comprises a LiNi a Co b M( 1-a-b )O2 compound, 0.9≤a<1.0, 0<b<0.1, and a+b<1.0, M includes at least one of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, La and Nb; the coating layer is coated on at least a portion of the surface of the core portion, the coating layer includes bismuth and titanium, and the ratio of the molar percentage of the bismuth element to the molar percentage of the titanium element is (0.1 to 2.0):1.
[0056] The core portion includes a molecular formula of LiNi a Co b M( 1-a-b )O2 compounds, which are layered transition metal oxides with high nickel content, 0.9≤a<1.0. When layered transition metal oxides are used in battery cells, volume changes may occur during the battery cell charge and discharge cycle, resulting in lattice collapse, and when the nickel content is high, the volume change is more obvious, which makes the material have the risk of pulverization.
[0057] In order to improve the performance of the layered transition metal oxide, the embodiment of the present application considers that a coating layer is provided on its outer surface, the layered transition metal oxide is used as the core, and the coating layer is coated on at least part of the outer surface of the core, so as to form a core-shell structure, and the coating layer can protect the core, reduce the risk of side reactions caused by direct contact between the layered transition metal oxide and the electrolyte in the core, and is conducive to improving the cycle life and storage life; and the coating layer includes bismuth and titanium elements, and on the basis of adjusting the molar percentage of the bismuth element to the molar percentage of the titanium element to be (0.1 to 2.0): 1, the bismuth element and the titanium element are more likely to form a perovskite structure, which is conducive to the insertion or extraction of lithium ions from the perovskite structure, and in the process of lithium ion insertion or extraction, the structure of the coating layer is relatively stable, the amplitude of volume change is small, and the structural change of the positive electrode active material is reduced, which can effectively improve the overall structural stability of the positive electrode active material and improve the cycle life and storage life of the positive electrode active material when applied to the battery cell. The perovskite structure formed by the above materials has a very high ionic conductivity, which is conducive to improving the rate performance of the positive electrode active material.
[0058] The coating layer of the embodiment of the present application can form a perovskite material, such as a bismuth-type perovskite material bismuth titanate, by regulating the molar percentage of bismuth and titanium elements. Of course, it may also form lithium titanate, lithium bismuthate, and the like. The coating layer comprising the above-mentioned materials can provide capacity for the positive electrode active material on the basis of improving the cycle life and storage life, thereby increasing the overall capacity of the positive electrode active material. Since bismuth titanate has better coating performance and is more conducive to improving the structural stability of the positive electrode active material, in some embodiments, the ratio of the molar percentage of the bismuth element to the molar percentage of the titanium element is (0.1 to 1.0): 1. The molar percentage of the titanium element is the same as or even relatively higher than the molar percentage of the bismuth element, which is more conducive to the formation of a perovskite structure such as bismuth titanate.
[0059] Exemplarily, the ratio of the molar percentage of the bismuth element to the molar percentage of the titanium element can be 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 4 / 3:1, 1.35:1, 1.40:1, 1.45:1, 1.50:1, 1.55:1, 1.60:1, 1.65:1, 1.70:1, 1.75:1, 1.80:1, 1.85:1, 1.90:1, 1.95:1, 2.00:1 or a range consisting of any two of the above values.
[0060] In the embodiment of the present application, the material of the coating layer and the content of each element are well known in the art, and can be detected by equipment and methods well known in the art, for example, with reference to EPA6010D-2014, tested by inductively coupled plasma atomic emission spectrometry, and measured by plasma atomic emission (ICP-OES, instrument model: Thermo ICAP7400). First, weigh 0.4g of the positive electrode active material and add 10ml (50% concentration) of aqua regia thereto. Then place it on a plate at 180°C for 30min. After digestion on the plate, dilute to a volume of 100mL, and use the standard curve method for quantitative testing.
[0061] The implementation manner of the present application can further select the core material so that the core material and the coating layer can play a better synergistic role and improve the cycle life and storage life of the battery cell.
[0062] In some embodiments, 0.9<a<0.98; optionally, 0.92≤a<0.98. The relatively high molar amount of nickel can significantly increase the capacity of the layered transition metal oxide, and in combination with the coating layer, can improve the overall structural stability of the positive electrode active material.
[0063] Illustratively, a may be 0.9, 0.905, 0.91, 0.915, 0.92, 0.925, 0.93, 0.935, 0.94, 0.945, 0.95, 0.955, 0.96, 0.965, 0.97, 0.975, 0.98, or a range consisting of any two of the foregoing values.
[0064] In some embodiments, b≥1-ab. The molar amount of cobalt Co is greater than the molar amount of the M element, which is beneficial to further stabilize the structure of the layered transition metal oxide, reduce the risk of cation mixing, and improve the cycle performance of the material; and Co can participate in the charge and discharge reaction in the operating voltage range of 2.8V to 4.25V, which is beneficial to improve the capacity.
[0065] In some embodiments, M includes at least one of Mn, Al, XX, XX, and XX.
[0066] Exemplarily, the core portion includes a molecular formula of LiNi 0.91 Co 0.05 M 0.04 O2、LiNi 0.92 Co 0.04 M 0.04 O2、LiNi 0.92 Co 0.05 M 0.03 O2、LiNi 0.92 Co 0.06 M 0.02 O2、LiNi 0.93 Co 0.03 M 0.02 O2 and LiNi 0.93 Co 0.025 M 0.025 At least one compound in O2.
[0067] The coating layer has ion conductivity, but it may not have electrochemical activity. Its addition amount has a certain influence on the coating performance. For example, when the coating layer is added in too little amount, the protective effect of the coating layer on the core is poor. As the amount of the coating layer added increases, the protective effect of the coating layer on the core is enhanced. However, when the coating layer is added in too much amount, it may occupy too much space because the coating layer does not have electrochemical activity. In order to improve the protective effect of the coating layer on the core, reduce the risk of the core being corroded by the electrolyte, and increase the energy density, in some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the core is A%, the mass percentage of the coating layer is B%, and 99≤A / B<1000. Optionally, 99≤A / B<300.
[0068] Illustratively, the ratio of the mass percentage of the core to the mass percentage of the coating can be 99, 99.01, 99.05, 99.1, 99.15, 99.2, 99.25, 99.3, 99.35, 99.4, 99.45, 99.5, 99.55, 99.6, 99.65, 99.7, 99.75, 99.8, 99.85, 99.9, 99.95, 100, 200, 300, 400, 500, 600, 700, 800, 900, 950, 990 or a range consisting of any two of the above values.
[0069] In some embodiments, 99≤A<100. For example, the mass percentage of the core portion can be 99%, 99.01%, 99.05%, 99.1%, 99.15%, 99.2%, 99.25%, 99.3%, 99.35%, 99.4%, 99.45%, 99.5%, 99.55%, 99.6%, 99.65%, 99.7%, 99.75%, 99.8%, 99.85%, 99.9%, 99.95% or a range consisting of any two of the above values.
[0070] In some embodiments, 0<B≤1. For example, the mass percentage of the coating layer can be 0.01%, 0.02%, 0.05%, 0.08%, 0.10%, 0.12%, 0.15%, 0.18%, 0.20%, 0.22%, 0.25%, 0.28%, 0.30%, 0.32%, 0.35%, 0.38%, 0.40%, 0.42%, 0.45%, 0.48%, 0.50%, 0.52%, 0.55%, 0.58%, 0.60%, 0.62%, 0.65%, 0.68%, 0.70%, 0.72%, 0.75%, 0.80%, 0.85%, 0.90%, 0.92%, 0.95%, 0.98%, 0.99%, 1% or a range consisting of any two of the above values.
[0071] In some embodiments, the coating layer has a thickness of 1 nm to 100 nm. When the coating layer has a thickness within the above range, it can provide good protection for the core, improve the overall structural stability of the positive electrode active material, and the coating layer will not occupy too much space, which is beneficial to improving the energy density.
[0072] In the embodiments of the present application, the thickness of the coating layer has a well-known meaning in the art and can be detected using equipment and methods commonly used in the art, such as ion polishing cross-sectional morphology analysis (CP) detection of the sample.
[0073] In order to further improve the cycle life and storage life, the embodiments of the present application can make the structure of the positive electrode active material more stable by selecting relevant parameters such as the particle size of the positive electrode active material, and the overall structural stability of the positive electrode active material is higher during the cycle process.
[0074] In some embodiments, the volume distribution particle sizes Dv10, Dv50 and Dv90 of the positive electrode active material satisfy: 0.5≤(Dv90-Dv10) / Dv50≤1.5; optionally, 0.8≤(Dv90-Dv10) / Dv50≤1.4. (Dv90-Dv10) / Dv50 can be expressed as the particle size distribution span, which can be understood as the width of the particle size distribution. When span is within the above range, the particle size distribution of the positive electrode active material is relatively concentrated. When the positive electrode slurry is coated to form a positive electrode film layer, the positive electrode slurry is relatively stable and is not prone to gelation. In the compaction process of forming the positive electrode film layer, the structure of the positive electrode active material is relatively stable and is not easy to be crushed. Moreover, the positive electrode active material is not prone to failure during the cycle.
[0075] Illustratively, span can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, or a range consisting of any two of the above values.
[0076] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material satisfies: 2.5μm≤Dv50≤15μm; optionally, 3μm≤Dv50≤12μm. When the volume distribution particle size Dv50 of the positive electrode active material is within the above range, the structural stability of the positive electrode active material during the cycle process can be improved, and the positive electrode active material is not prone to cracking, thereby reducing the risk of battery cell failure caused by cracking-induced corrosion at the boundary of the positive electrode active material to form a rock salt phase, and reducing the risk of excessive contact between the positive electrode active material and the electrolyte, resulting in increased corrosion.
[0077] In the embodiment of the present application, Dv10, Dv50, and Dv90 of the particles have meanings well known in the art. For example, Dv10 refers to the particle size corresponding to 10% of the volume distribution, Dv50 refers to the particle size corresponding to 50% of the volume distribution, and Dv90 refers to the particle size corresponding to 90% of the volume distribution. The above particle sizes can be detected using equipment and methods commonly used in the art. For example, according to the test standard GB / T 19077-2016, a certain amount of positive electrode active material sample is taken, and the particle size distribution of the positive electrode active material is measured by a Mastersizer 2000E laser particle size analyzer to obtain Dv10, Dv90, and Dv50, and (Dv90-Dv10) / Dv50 is calculated.
[0078] Illustratively, the volume distribution particle size Dv50 of the positive electrode active material can be 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm, 5.5μm, 6.0μm, 6.5μm, 7.0μm, 7.5μm, 8.0μm, 8.5μm, 9.0μm, 9.5μm, 10.0μm, 10.5μm, 11.0μm, 11.5μm, 12.0μm, 12.5μm, 13.0μm, 13.5μm, 14.0μm, 14.5μm, 15μm, or a range consisting of any two of the above values.
[0079] In some embodiments, the specific surface area of the positive electrode active material satisfies BET of 0.34 m 2 / g≤BET≤1.2m 2 / g; optionally, 0.5m 2 / g≤BET≤1.0m 2 When the specific surface area of the positive electrode active material is within the above range, the positive electrode active material can expose a relatively large active specific surface area, which is beneficial to the performance of the capacity of the positive electrode active material.
[0080] For example, the specific surface area BET of the positive electrode active material may be 0.34 m 2 / g, 0.35m 2 / g, 0.38m 2 / g, 0.40m 2 / g, 0.42m 2 / g, 0.45m 2 / g, 0.50m 2 / g, 0.55m 2 / g, 0.60m 2 / g, 0.65m 2 / g, 0.70m 2 / g, 0.75m 2 / g, 0.80m 2 / g, 0.85m 2 / g, 0.90m 2 / g, 0.95m 2 / g, 1.00m 2 / g, 1.05m 2 / g, 1.10m 2 / g, 1.15m 2 / g, 1.20m 2 / g or a range consisting of any two of the above values.
[0081] In the embodiment of the present application, the specific surface area BET of the positive electrode active material has a well-known meaning in the art and can be detected by using the commonly used equipment and methods in the art. According to the test standard GB / T 19587-2017, the specific surface area is calculated by the BET (BrunauerEmmett Teller) method. A certain amount of positive electrode active material sample is taken and the specific surface area is tested by the Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.
[0082] In order to further improve the cycle life and storage life, the embodiments of the present application can improve the structural stability of the positive electrode active material by selecting relevant parameters such as the particle morphology of the positive electrode active material, thereby making the positive electrode active material have higher structural stability during the cycle process.
[0083] In some embodiments, the positive electrode active material includes polycrystalline agglomerate particles. In order to improve the structural stability of the positive electrode active material, optionally, the volume distribution particle size Dv50 of the positive electrode active material is 4.0 μm to 15.0 μm. When the volume distribution particle size Dv50 of the positive electrode active material is within the above range, its particle size is relatively large, but not too large, which is conducive to capacity development and can improve its structural stability.
[0084] Illustratively, the volume distribution particle size Dv50 of the positive electrode active material can be 4.0μm, 4.5μm, 5.0μm, 5.5μm, 6.0μm, 6.5μm, 7.0μm, 7.5μm, 8.0μm, 8.5μm, 9.0μm, 9.5μm, 10.0μm, 10.5μm, 11.0μm, 11.5μm, 12.0μm, 12.5μm, 13.0μm, 13.5μm, 14.0μm, 14.5μm, 15μm, or a range consisting of any two of the above values.
[0085] Optionally, the primary particle size D1 of the polycrystalline agglomerate particles satisfies: 0.1 μm≤D1≤0.4 μm. A relatively small primary particle size D1 is conducive to agglomeration into spherical or quasi-spherical positive electrode active materials, thereby improving the structural stability of the positive electrode active materials.
[0086] Exemplarily, the primary particle size D1 of the polycrystalline agglomerate particles can be 0.20μm, 0.21μm, 0.22μm, 0.23μm, 0.24μm, 0.25μm, 0.26μm, 0.27μm, 0.28μm, 0.29μm, 0.30μm, 0.31μm, 0.32μm, 0.33μm, 0.34μm, 0.35μm, 0.36μm, 0.37μm, 0.38μm, 0.39μm, 0.40μm or a range consisting of any two of the above values.
[0087] In some embodiments, the positive electrode active material includes single crystal particles or quasi-single crystal particles, the particle size of the single crystal particles or the quasi-single crystal particles is relatively small, and the structural stability during the cycle process is improved. In order to further improve the structural stability of the positive electrode active material, optionally, the volume distribution particle size Dv50 of the positive electrode active material satisfies: 2.0μm≤Dv50≤4.0μm.
[0088] Illustratively, the volume distribution particle size Dv50 of the positive electrode active material can be 2.0 μm, 2.2 μm, 2.3 μm, 2.5 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4.0 μm, or a range consisting of any two of the above values.
[0089] Optionally, the primary particle size D2 of the single crystal particles or the quasi-single crystal particles satisfies: 0.7 μm≤D2≤2.0 μm. The primary particle size D2 of the single crystal particles or the quasi-single crystal particles is relatively small, which is beneficial to improving the structural stability of the positive electrode active material.
[0090] Exemplarily, the primary particle size D2 of single crystal particles or quasi-single crystal particles can be 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm or a range consisting of any two of the above values.
[0091] In the embodiment of the present application, the primary particle size D1 of the positive electrode active material has a well-known meaning in the art and can be detected by using equipment and methods commonly used in the art. For example, a scanning electron microscope (SEM) is performed on the sample, and the particle size of the sample is intuitively obtained based on the obtained SEM spectrum. A plurality of samples are taken for SEM detection, and the multiple particle sizes measured are averaged to obtain the average particle size.
[0092] Method for preparing positive electrode active material
[0093] In a second aspect, the embodiments of the present application provide a method for preparing a positive electrode active material, and the positive electrode active material can be prepared by a co-precipitation method.
[0094] The method comprises:
[0095] Step S100, weighing a lithium source, a nickel source, a cobalt source and a M source in a corresponding stoichiometric ratio according to a target component;
[0096] Step S200, mixing the lithium source, the nickel source, the cobalt source and the M source uniformly to obtain a raw material mixture;
[0097] Step S300, grinding, calcining, cooling, and crushing the raw material mixture in sequence to obtain a layered transition metal oxide intermediate;
[0098] Step S400, mixing the layered transition metal oxide intermediate and the coating material, calcining and cooling to obtain a positive electrode active material.
[0099] In step S100, the lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium oxalate.
[0100] In some embodiments, the nickel source includes at least one of nickel sulfate, nickel nitrate, or nickel chloride.
[0101] In some embodiments, the cobalt source includes at least one of cobalt sulfate, cobalt nitrate, or cobalt chloride.
[0102] In some embodiments, the M source includes at least one of sulfate, nitrate, chloride, oxide, and carbonate containing M. The M source includes at least one of a Mn source, an Al source, a B source, a Zr source, a Sr source, a Y source, a Sb source, a W source, a Ti source, a La source, and a Nb source.
[0103] The nickel source, cobalt source and M source may come from the same material or from different materials.
[0104] Before step S100, the nickel source, the cobalt source and the M source may be mixed in a solution state, and a suitable precipitant may be added to the solution so that the components that have been evenly mixed in the solution are co-precipitated according to a stoichiometric ratio to form a raw material intermediate. In step S100, the raw material intermediate and the lithium source are mixed, ground, calcined, cooled and crushed to obtain a layered transition metal oxide intermediate.
[0105] In step S200, the mixing time of each raw material can be 0.5h to 2h.
[0106] In step S300, the raw material mixture powder can be calcined in a pure oxygen atmosphere, and multiple calcinations can be used. The first calcination temperature is 300°C to 650°C, and the calcination time is 5h to 20h; the second calcination temperature is 600°C to 900°C, and the calcination time is 5h to 20h. The two calcinations can be pre-oxidized to eliminate internal defects of the material. Of course, one calcination can also be used, for example, calcining at 600°C to 900°C for 6h to 30h.
[0107] In step S400, the coating material includes a bismuth source and a titanium source. Optionally, the bismuth source may include at least one of bismuth oxide, bismuth carbonate, and bismuth nitrate; optionally, the titanium source may include at least one of titanium oxide, titanium carbonate, and titanium nitrate.
[0108] In some embodiments, the calcination temperature of the layered transition metal oxide intermediate and the coating material may be lower than the calcination temperature of the raw material mixture powder. In step S400, the calcination temperature of the layered transition metal oxide intermediate and the coating material after mixing may be 400°C to 750°C.
[0109] Battery Cell
[0110] In a third aspect, the embodiments of the present application also provide a battery cell.
[0111] A battery cell is also called a rechargeable battery or storage battery. It refers to a battery that can be used continuously by recharging the active material after the battery is discharged. Generally, a battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet. It mainly prevents the positive electrode and the negative electrode from short-circuiting, and allows active ions to pass through.
[0112] The battery cell comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer comprises a positive electrode active material according to any embodiment of the first aspect of the present application or a positive electrode active material prepared by the method described in any embodiment of the second aspect of the present application. Thus, the battery cell of the present application can improve the cycle life and storage life.
[0113] [Positive electrode]
[0114] In some embodiments, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0115] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total weight of the positive electrode film layer, the mass percentage of the positive electrode conductive agent is ≤5wt%.
[0116] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. The present application does not particularly limit the type of the positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total weight of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5wt%.
[0117] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0118] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the composite positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0119] [Negative electrode]
[0120] In some embodiments, the battery cell further includes a negative electrode tab.
[0121] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0122] The negative electrode active material may be a negative electrode active material for a battery cell known in the art. As an example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy material.
[0123] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5wt%.
[0124] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤5wt%.
[0125] In some embodiments, the negative electrode film layer may further include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the other additives is ≤2wt%.
[0126] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0127] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0128] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (for example, composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0129] [Electrolyte]
[0130] In some embodiments, the battery cell further includes an electrolyte.
[0131] During the charge and discharge process of the battery cell, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to actual needs.
[0132] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not specifically limited and can be selected according to actual needs.
[0133] As an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0134] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0135] In some embodiments, the electrolyte may further include additives, for example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.
[0136] [Isolation film]
[0137] In some embodiments, the battery cell further includes a separator.
[0138] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0139] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0140] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.
[0141] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0142] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0143] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0144] In some embodiments, Figure 2As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0145] The preparation method of the battery cell of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery cell is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0146] In some embodiments of the present application, the battery cells according to the present application may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module.
[0147] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0148] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0149] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0150] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0151] Electrical devices
[0152] The fourth aspect of the embodiment of the present application provides an electric device, which includes at least one of the battery cells, battery modules or battery packs of the present application. The battery cells, battery modules or battery packs can be used as the power source of the electric device, and can also be used as the energy storage unit of the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0153] The electrical device may select a battery cell, a battery module or a battery pack according to its usage requirements.
[0154] Figure 6 Schematic diagram of an exemplary electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device 6 for high power and high energy density, a battery pack or a battery module may be used.
[0155] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0156] Example
[0157] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0158] Example A Preparation of positive electrode active material
[0159] The precursor P0 of high-nickel ternary material was prepared by co-precipitation method.
[0160] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L solution (the solvent was water) in a molar ratio of 9.2:0.4:0.4, and the solution was placed in a reactor and the particle size and micromorphology were adjusted by controlling the reaction time to 12 h to 24 h, the reaction temperature to 40 ° C to 70 ° C, the pH value to 11 to 13 and the ammonia concentration to 0.2 mol / L to 0.6 mol / L. Finally, P0(Ni 0.92Co 0.04 Mn 0.04 (OH)2), its volume distribution particle size Dv50 is 10μm and span is about 1.25.
[0161] Lithium hydroxide and P0 were mixed evenly in a molar ratio of 1.03:1 and placed in a box furnace and sintered at 800 °C for 15 h to obtain the core LiNi 0.92 Co 0.04 Mn 0.04 O2; after cooling and crushing, the coating material (1200ppm Bi2O3+900ppmTiO2) was added, and then placed in a high-speed mixer and mixed at 200r / min for 2h, and sintered at 650℃ in an oxygen atmosphere for 13h to obtain the positive electrode active material.
[0162] Examples B-1 to B-4
[0163] The positive electrode active material was prepared by a method similar to that of Example A. The difference from Example A was that the amount of coating material added was adjusted in Examples B-1 to B-4.
[0164] Examples C-1 to C-5
[0165] The positive electrode active material was prepared by a method similar to that of Example A. The difference from Example A is that Examples C-1 to C-5 adjusted the ratio of the bismuth source and the titanium source in the coating material.
[0166] Examples D-1 to D-3
[0167] The positive electrode active material was prepared by a method similar to that of Example A. The difference from Example A is that the material type of the core portion was adjusted in Examples D-1 to D-3.
[0168] Examples F-1 to F-5
[0169] The positive electrode active material was prepared by a method similar to that of Example A. The difference from Example A is that the sintering temperature and sintering time of the preparation process were adjusted in Examples F-1 to F-5 to adjust at least one of the particle size and morphology.
[0170] Example F-1
[0171] The preparation process conditions of the positive electrode active material are adjusted as follows:
[0172] The precursor P0 of high-nickel ternary material was prepared by co-precipitation method.
[0173] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L solution (the solvent was water) in a molar ratio of 9.2:0.4:0.4, and the solution was placed in a reactor and the particle size and micromorphology were adjusted by controlling the reaction time to 12 h to 24 h, the reaction temperature to 40 ° C to 70 ° C, the pH value to 11 to 13 and the ammonia concentration to 0.2 mol / L to 0.6 mol / L. Finally, P0(Ni 0.92 Co 0.04 Mn 0.04 (OH)2), its volume distribution particle size Dv50 is 8μm, and span is about 1.3.
[0174] Lithium hydroxide and P0 were mixed evenly in a molar ratio of 1.03:1 and placed in a box furnace for sintering at 790 °C for 15 h to obtain the core LiNi 0.92 Co 0.04 Mn 0.04 O2; after cooling and crushing, the coating material (1200ppm Bi2O3+900ppmTiO2) was added, and then placed in a high-speed mixer and mixed at 200r / min for 2h, and sintered at 650℃ in an oxygen atmosphere for 13h to obtain the positive electrode active material.
[0175] Example F-2
[0176] The preparation process conditions of the positive electrode active material are adjusted as follows:
[0177] The precursor P0 of high-nickel ternary material was prepared by co-precipitation method.
[0178] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L solution (the solvent was water) in a molar ratio of 9.2:0.4:0.4, and the solution was placed in a reactor and the particle size and micromorphology were adjusted by controlling the reaction time to 12 h to 24 h, the reaction temperature to 40 ° C to 70 ° C, the pH value to 11 to 13 and the ammonia concentration to 0.2 mol / L to 0.6 mol / L. Finally, P0(Ni 0.92 Co 0.04 Mn 0.04 (OH)2), its volume distribution particle size Dv50 is 9.2μm, and span is about 1.25.
[0179] Lithium hydroxide and P0 were mixed evenly in a molar ratio of 1.03:1 and placed in a box furnace and sintered at 800 °C for 15 h to obtain the core LiNi 0.92 Co 0.04 Mn 0.04 O2; after cooling and crushing, the coating material (1200ppm Bi2O3+900ppmTiO2) was added, and then placed in a high-speed mixer and mixed at 200r / min for 2h, and sintered at 650℃ in an oxygen atmosphere for 13h to obtain the positive electrode active material.
[0180] Example F-3
[0181] The preparation process conditions of the positive electrode active material are adjusted as follows:
[0182] The precursor P0 of high-nickel ternary material was prepared by co-precipitation method.
[0183] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L solution (the solvent was water) in a molar ratio of 9.2:0.4:0.4, and the solution was placed in a reactor and the particle size and micromorphology were adjusted by controlling the reaction time to 12 h to 24 h, the reaction temperature to 40 ° C to 70 ° C, the pH value to 11 to 13 and the ammonia concentration to 0.2 mol / L to 0.6 mol / L. Finally, P0(Ni 0.92 Co 0.04 Mn 0.04 (OH)2), its volume distribution particle size Dv50 is 9.8μm and span is about 1.33.
[0184] Lithium hydroxide and P0 were mixed evenly in a molar ratio of 1.03:1 and placed in a box furnace and sintered at 800 °C for 15 h to obtain the core LiNi 0.92 Co 0.04 Mn 0.04 O2; after cooling and crushing, the coating material (1200ppm Bi2O3+900ppmTiO2) was added, and then placed in a high-speed mixer and mixed at 200r / min for 2h, and sintered at 650℃ in an oxygen atmosphere for 13h to obtain the positive electrode active material.
[0185] Example F-4
[0186] The preparation process conditions of the positive electrode active material are adjusted as follows:
[0187] The precursor P0 of high-nickel ternary material was prepared by co-precipitation method.
[0188] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L solution (the solvent was water) in a molar ratio of 9.2:0.4:0.4, and the solution was placed in a reactor and the particle size and micromorphology were adjusted by controlling the reaction time to 12 h to 24 h, the reaction temperature to 40 ° C to 70 ° C, the pH value to 11 to 13 and the ammonia concentration to 0.2 mol / L to 0.6 mol / L. Finally, P0(Ni 0.92 Co 0.04 Mn 0.04 (OH)2), its volume distribution particle size Dv50 is 16μm and span is about 1.2.
[0189] Lithium hydroxide and P0 were mixed evenly in a molar ratio of 1.03:1 and placed in a box furnace for sintering at 820°C for 15h to obtain the core LiNi 0.92 Co 0.04 Mn 0.04 O2; after cooling and crushing, the coating material (1200ppm Bi2O3+900ppmTiO2) was added, and then placed in a high-speed mixer and mixed at 200r / min for 2h, and sintered at 650℃ in an oxygen atmosphere for 13h to obtain the positive electrode active material.
[0190] Example F-5
[0191] The preparation process conditions of the positive electrode active material are adjusted as follows:
[0192] The precursor P0 of high-nickel ternary material was prepared by co-precipitation method.
[0193] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L solution (the solvent was water) in a molar ratio of 9.2:0.4:0.4, and the solution was placed in a reactor and the particle size and micromorphology were adjusted by controlling the reaction time to 12 h to 24 h, the reaction temperature to 40 ° C to 70 ° C, the pH value to 11 to 13 and the ammonia concentration to 0.2 mol / L to 0.6 mol / L. Finally, P0(Ni 0.92 Co 0.04 Mn 0.04 (OH)2), its volume distribution particle size Dv50 is 3.8μm (single crystal particles), and the span is about 1.4.
[0194] Lithium hydroxide and P0 were mixed evenly in a molar ratio of 1.03:1 and placed in a box furnace for sintering at 840 °C for 15 h to obtain the core LiNi 0.92 Co 0.04 Mn 0.04 O2; after cooling and crushing, the coating material (1200ppm Bi2O3+900ppmTiO2) was added, and then placed in a high-speed mixer and mixed at 200r / min for 2h, and sintered at 650℃ in an oxygen atmosphere for 13h to obtain the positive electrode active material.
[0195] Comparative Example M
[0196] The precursor P0 of high-nickel ternary material was prepared by co-precipitation method.
[0197] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L solution (the solvent was water) in a molar ratio of 9.2:0.4:0.4, and the solution was placed in a reactor and the particle size and micromorphology were adjusted by controlling the reaction time to 12 h to 24 h, the reaction temperature to 40 ° C to 70 ° C, the pH value to 11 to 13 and the ammonia concentration to 0.2 mol / L to 0.6 mol / L. Finally, P0(Ni 0.92 Co 0.04 Mn 0.04 (OH)2), its volume distribution particle size Dv50 is 10μm and span is about 1.25.
[0198] Lithium hydroxide and P0 were mixed evenly in a molar ratio of 1.03:1 and placed in a box furnace for sintering at 800 °C for 15 h. After cooling and crushing, the core LiNi 0.92 Co 0.04 Mn 0.04 O2.
[0199] Comparative Example N
[0200] The precursor P0 of high nickel ternary material was prepared by coprecipitation method. Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L solution (solvent was water) in a molar ratio of 89:11:10, and the solution was placed in a reactor and the particle size and micromorphology were adjusted by controlling the reaction time to 12h to 24h, the reaction temperature to 40℃ to 70℃, the pH value to 11 to 13 and the ammonia concentration to 0.2mol / L to 0.6mol / L. The final prepared P0 (Ni 0.89 Co 0.10 Mn 0.1 (OH)2), its volume distribution particle size Dv50 is 10μm and span is about 1.25.
[0201] Lithium hydroxide and P0 were mixed evenly in a molar ratio of 1.03:1 and placed in a box furnace and sintered at 850°C for 15h to obtain the core LiNi 0.89 Co 0.10 Mn 0.1 O2; after cooling and crushing, the coating material (1200ppm Bi2O3+900ppmTiO2) was added, and then placed in a high-speed mixer and mixed at 200r / min for 2h, and sintered at 650℃ in an oxygen atmosphere for 13h to obtain the positive electrode active material.
[0202] Comparative Example P
[0203] The precursor P0 of high-nickel ternary material was prepared by co-precipitation method.
[0204] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L solution (the solvent was water) in a molar ratio of 9.2:0.4:0.4, and the solution was placed in a reactor and the particle size and micromorphology were adjusted by controlling the reaction time to 12 h to 24 h, the reaction temperature to 40 ° C to 70 ° C, the pH value to 11 to 13 and the ammonia concentration to 0.2 mol / L to 0.6 mol / L. Finally, P0(Ni 0.92 Co 0.04 Mn 0.04 (OH)2), its volume distribution particle size Dv50 is 10μm and span is about 1.25.
[0205] Lithium hydroxide and P0 were mixed evenly in a molar ratio of 1.03:1 and placed in a box furnace and sintered at 800 °C for 15 h to obtain the core LiNi 0.92 Co 0.04 Mn 0.04 O2; after cooling and crushing, 2000ppm of coating material (Bi2O3+TiO2, where the molar ratio of Bi to Ti is 0.08:1) is added, and then placed in a high-speed mixer and mixed at 200r / min for 2h, and sintered at 650℃ in an oxygen atmosphere for 13h to obtain the positive electrode active material.
[0206] Example 1 Preparation of lithium ion battery
[0207] 1. Preparation of positive electrode
[0208] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.
[0209] The positive electrode active material prepared in Example A, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride (PVDF) were uniformly mixed in a proper amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 96:2:2 to obtain a positive electrode slurry; the positive electrode slurry was coated on the positive electrode current collector aluminum foil, and the positive electrode sheet was obtained through drying, cold pressing, slitting, cutting and other processes.
[0210] 2. Preparation of negative electrode sheet
[0211] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0212] Artificial graphite as the negative electrode active material, conductive carbon black as the conductive agent, and styrene butadiene rubber (SBR) as the adhesive are mixed evenly in deionized water to prepare a negative electrode slurry. The mass ratio of artificial graphite, conductive carbon black as the conductive agent, and styrene butadiene rubber (SBR) as the adhesive in the solid components of the negative electrode slurry is 92:4:4. The negative electrode slurry is coated on the current collector copper foil and dried at 85°C and cold pressed to obtain a negative electrode sheet containing a negative electrode active material layer.
[0213] 3. Preparation of electrolyte
[0214] In an environment with a water content of less than 10 ppm, organic solvents ethylene carbonate EC and diethyl carbonate DEC are mixed in a volume ratio of 3:7 to obtain an electrolyte solvent, and then lithium salt lithium hexafluorophosphate and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0215] 4. Preparation of lithium-ion batteries
[0216] The positive electrode sheet, polyethylene PE separator, and negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0217] Other embodiments and comparative examples use a method similar to that of embodiment 1 to prepare lithium ion batteries. The difference from embodiment 1 is that some parameters are adjusted, as follows:
[0218] Comparative Example 1 uses the positive electrode active material of Comparative Example M.
[0219] Comparative Example 2 uses the positive electrode active material of Comparative Example N.
[0220] Comparative Example 3 uses the positive electrode active material of Comparative Example P.
[0221] Example 2-1 uses the positive electrode active material of Example B-1.
[0222] Example 2-2 uses the positive electrode active material of Example B-2.
[0223] Example 2-3 uses the positive electrode active material of Example B-3.
[0224] Example 2-4 uses the positive electrode active material of Example B-4.
[0225] Example 3-1 uses the positive electrode active material of Example C-1.
[0226] Example 3-2 uses the positive electrode active material of Example C-2.
[0227] Example 3-3 uses the positive electrode active material of Example C-3.
[0228] Example 3-4 uses the positive electrode active material of Example C-4.
[0229] Example 3-5 uses the positive electrode active material of Example C-5.
[0230] Example 4-1 uses the positive electrode active material of Example D-1.
[0231] Example 4-2 uses the positive electrode active material of Example D-2.
[0232] Example 4-3 uses the positive electrode active material of Example D-3.
[0233] Example 5-1 uses the positive electrode active material of Example F-1.
[0234] Example 5-2 uses the positive electrode active material of Example F-2.
[0235] Example 5-3 uses the positive electrode active material of Example F-3.
[0236] Example 5-4 uses the positive electrode active material of Example F-4.
[0237] Example 5-5 uses the positive electrode active material of Example F-5.
[0238] The relevant parameters of the embodiments and comparative examples are shown in Table 1.
[0239] Test Section
[0240] 1. Cycle life test of lithium-ion batteries
[0241] At 25°C, the lithium-ion batteries prepared in the embodiments and comparative examples were charged at a constant current of 0.5C to a charge cut-off voltage of 4.25V, then charged at a constant voltage to a current of ≤0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.33C to a discharge cut-off voltage of 2V, left to stand for 5 minutes. This is a charge and discharge cycle. The battery was subjected to a cyclic charge and discharge test according to this method until the battery capacity decayed to 80%. The number of cycles at this time is the cycle life of the battery at 25°C.
[0242] 2. Storage life test of lithium-ion batteries
[0243] At 45°C, charge to 4.25V at a constant current of 1C, then charge at a constant voltage of 4.25V until the current drops to 0.05C, and then discharge to 2.8V at a constant current of 1C to obtain the first-cycle discharge specific capacity (Cd1); charge to 4.25V at a constant current of 1C, then charge at a constant voltage of 4.25V until the current drops to 0.05C, keep the full charge state for 15 days, and then discharge to 2.8V at a constant current of 1C to obtain the discharge specific capacity after 15 days (Cd15); (Cd15) / (Cd1) is the storage retention rate for 15 days.
[0244] Test Results
[0245] The test results are shown in Table 1
[0246] Table 1
[0247]
[0248] In Table 1, the mass content A% refers to the mass percentage of the core portion relative to the total mass of the positive electrode active material.
[0249] The mass content B% refers to the mass percentage of the coating layer relative to the total mass of the positive electrode active material.
[0250] As shown in Table 1, the positive electrode active material in Comparative Example 1 is a high-nickel ternary material LiNi 0.92 Co 0.04 Mn 0.04 O2, its structural stability is poor; compared with comparative example 1, comparative example 3 has a high nickel ternary material LiNi 0.92 Co 0.04 Mn 0.04 A coating layer is set on the surface of O2, and the molar ratio of Bi and Ti elements in the coating layer is 0.08:1. The molar amount of Bi element is low, and it is not easy to form a perovskite structure. The surface layer can only form a lithium titanate fast ion conductor, and the effect of improving the structural stability of the high-nickel ternary material is weak.
[0251] The nickel content of the ternary material of the positive electrode active material in Comparative Example 2 is relatively low (LiNi 0.89 Co 0.10 Mn 0.1 O2), the overall capacity is low, and the life is better than that of 9 series ternary materials. Although its service life can be further improved by coating, its structure is more stable than that of high nickel materials, and the improvement in life is not obvious.
[0252] The embodiment of the present application provides a coating layer on the surface of the high-nickel ternary material to protect the core, reduce the risk of side reactions caused by direct contact between the layered transition metal oxide in the core and the electrolyte, and is beneficial to improving the cycle life and storage life; and the coating layer includes bismuth and titanium elements, and on the basis of adjusting the ratio of the molar percentage of the bismuth element to the molar percentage of the titanium element to be (0.1 to 2.0): 1, the bismuth and titanium elements are more likely to form a perovskite structure, which is beneficial to the embedding or extraction of lithium ions from the perovskite structure, and in the process of embedding or extraction of lithium ions, the structure of the coating layer is relatively stable, the amplitude of volume change is small, and the structural change of the positive electrode active material is reduced, which can effectively improve the overall structural stability of the positive electrode active material and improve the cycle life and storage life of the positive electrode active material when applied to battery cells.
[0253] Figure 7 and Figure 8 A schematic diagram showing the positive electrode active material of Example A, Figure 7 and Figure 8This is a SEM image of a positive electrode active material, in which the surface of the core portion is covered with a coating layer.
[0254] Fig. 9 The XRD diagram of the positive electrode active material shows that the sharp peaks indicate good crystallinity, the (003) and (104) peak ratios are above 4.9, and the (108) and (110) peaks are well split, all of which indicate that the coating layer has not destroyed the layered structure of the material.
[0255] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A positive electrode active material comprising: The core portion includes a molecular formula of LiNi a Co b M( 1-a-b )O2, 0.9≤a<1.0, 0<b<0.1, and a+b<1.0, M comprises at least one of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, La and Nb; and A coating layer is coated on at least a portion of the surface of the core portion, wherein the coating layer includes bismuth and titanium elements, and the ratio of the molar percentage content of the bismuth element to the molar percentage content of the titanium element is (0.1 to 2.0):
1.
2. The positive electrode active material according to claim 1, wherein The ratio of the molar percentage content of the bismuth element to the molar percentage content of the titanium element is (0.1 to 1.0):
1.
3. The positive electrode active material according to claim 1 or 2, wherein The coating layer includes at least one of bismuth titanate, lithium titanate and lithium bismuthate; optionally, the coating layer includes bismuth titanate.
4. The positive electrode active material according to any one of claims 1 to 3, wherein 0.9<a<0.98; Optionally, 0.92≤a<0.98; and / or b≥1-ab; Optionally, the core portion includes a LiNi 0.91 Co 0.05 M 0.04 O2、LiNi 0.92 Co 0.04 M 0.04 O2、LiNi 0.92 Co 0.05 M 0.03 O2、LiNi 0.92 Co 0.06 M 0.02 O2、LiNi 0.93 Co 0.03 M 0.02 O2 and LiNi 0.93 Co 0.025 M 0.025 At least one compound in O2.
5. The positive electrode active material according to any one of claims 1 to 4, wherein Based on the total mass of the positive electrode active material, the mass percentage of the core portion is A%, the mass percentage of the coating layer is B%, and 99≤A / B<1000; optionally, 99≤A / B<300; Further optionally, 99≤A<100; and / or 0<B≤1.
6. The positive electrode active material according to any one of claims 1 to 5, wherein The coating layer has a thickness of 1 nm to 100 nm.
7. The positive electrode active material according to any one of claims 1 to 6, wherein The positive electrode active material satisfies at least one of the following conditions: (1) The volume distribution particle sizes Dv10, Dv50 and Dv90 of the positive electrode active material satisfy the following conditions: 0.5≤(Dv90-Dv10) / Dv50≤1.5; optionally, 0.8≤(Dv90-Dv10) / Dv50≤1.4; (2) The volume distribution particle size Dv50 of the positive electrode active material satisfies: 2.0 μm ≤ Dv50 ≤ 15 μm; optionally, 3 μm ≤ Dv50 ≤ 12 μm; (3) The specific surface area of the positive electrode active material satisfies BET of 0.34 m 2 / g≤BET≤1.2m 2 / g; optionally, 0.5m 2 / g≤BET≤1.0m 2 / g.
8. The positive electrode active material according to any one of claims 1 to 7, wherein The positive electrode active material includes polycrystalline agglomerate particles; Optionally, The primary particle size D1 of the polycrystalline agglomerate particles satisfies: 0.1 μm≤D1≤0.4 μm; and / or The volume distribution particle size Dv50 of the polycrystalline agglomerate particles satisfies: 4.0 μm≤Dv50≤15.0 μm.
9. The positive electrode active material according to any one of claims 1 to 8, wherein The positive electrode active material includes single crystal particles or quasi-single crystal particles, Optionally, The primary particle size D2 of the single crystal particles or quasi-single crystal particles satisfies: 0.7 μm≤D2≤2.0 μm; and / or The volume distribution particle size Dv50 of the single crystal particles or quasi-single crystal particles satisfies: 2.0 μm≤Dv50≤4.0 μm. 10 . A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode active material according to claim 1 .
11. A battery cell comprising the positive electrode sheet according to claim 10.
12. A battery comprising the battery cell according to claim 11.
13. An electrical device comprising the battery as claimed in claim 12.
Citation Information
Patent Citations
Cathode materials, cathodes, and lithium secondary batteries containing spinel-structured lithium manganese-based cathode active materials
CN110582875A
Positive pole piece for secondary battery, secondary battery, battery module, battery pack and device
CN114256443A
Positive electrode active material for lithium secondary battery and lithium secondary battery comprising same
KR1020160023147A
Positive Electrode Material for Lithium Secondary Battery, Positive Electrode Including Same, and Lithium Secondary Battery
US20200335783A1
Cited By
Battery monomer, battery device and electric device
CN120221638A
Battery cells, battery devices and power-consuming devices
CN120221638B
Battery cell, battery device and electric device
CN122417861A